ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI - Siti Masrokhah; Santi Suciningtyas (Neraca, 2016)
This research title is â€œ Analysis of influence discipline, environment job, training education to employee performanceâ€ (Case Study in Department of Cooperatives, UKM, Trade and Industry Pemalang Regency)â€. This research target is : first, to know and analyse influence of discipline variable to employee performance variable, second, to know and analyse influence of environment job variable to employee performance variable, third, to know and analyse influence of education and training variable to employee performance variable, fourth, to know and analyse influence of discipline variable, environment job variable, training education variable to employee performance variable. With multiple linear regression analysis at this research obtained by result b1 = 0,290 showing influence which are significance of discipline variable (X1) equal 0,290 to employee performance, b2 = 0,118 showing influence which are significance of environment job variable (X2) equal 0,118 to employee performance, b3 = 0,672 showing influence which are significance of training education variable (X3) equal 0,672 to employee performance. While for the hypothesis examination in parcial used by t test, obstaned by value tcount for discipline variable (X1) equal to 4,269, environment job variable (X2) equal to 2,440, training education variable (X3) equal to 8,216 with criterion of ttables of equal to 1,996 used in this examination. And for examination as a whole be used by F test. Be obtained by F count equal to 33,637 with level significance of 0,000 far smaller than 0,05 and bigger than Ftable of equal to 2,75. Coefficient determinant (R2) equal to 60,8%, what mean that employee performance together be influenced by discipline variable, environment job variable, training education variable, while the remaining equal to 39,2% influenced by other variables that are not included in the model equations.